Breaking Bad News: A Small Group Session Teaching Communication Skills for Delivering Bad News - Maria van Zuilen; Panagiota Caralis; Lisa Granville (Association of American Medical Colleges, 2013)
Abstract Introduction Breaking bad news is a common yet difficult task that medical professionals are responsible for. At the University of Miami Miller School of Medicine, students are introduced to this topic relatively early on in their training in a small-group format. This 2-hour interactive small-group role play session was designed for medical students, but it has also been used with other levels of medical trainees (e.g., geriatric medicine fellows). Methods After a brief facilitator led discussion exploring the learners' understanding of and experience with delivering bad news, Buckman's six step model for delivering bad news is reviewed. Learners then participate in role-plays using a helping trio format, in which one student is the doctor, one is the patient, and one is the observer. Using this format, learners have the opportunity to give bad news, experience receiving bad news, and observe the delivery of bad news. Results We have successfully delivered this session for more than 12 years and have reached approximately 2000 students. For many years, this session was included in the first-year curriculum. Although students liked the session, some of the facilitators felt that the topic and the case used for role play were too difficult for students at this stage of training. During a reorganization of the curriculum, we chose to move the session to the last semester of their second year. Because students are a little more comfortable with medical terminology and interviewing, the session seems to work well as an introduction to this topic at this time in the curriculum. Discussion Breaking bad news is a difficult skill that can elicit significant distress among learners. As such, it is important for learners to practice this skill in a controlled environment, which affords time to address any distress that arises and the opportunity to receive supportive feedback on performance.